'The second mother': How the baby food industry captures science, health professions and civil society in France. Issue 2 (22nd December 2021) - Cossez, Emma; Baker, Philip; Mialon, Mélissa
Abstract: Most babies in France are fed with infant formula and then commercial complementary foods, many of which are ultra‐processed and harmful to health. Internationally, there is opposition by the baby food industry to the introduction of public health policies that would limit the marketing and consumption of such products. Our aim was to identify the key baby food industry actors, describe their history and corporate political activity (CPA) in France. We sourced publicly available information, which we triangulated with data from 10 semi‐structured interviews. Qualitative thematic analysis was undertaken simultaneously to data collection, guided by an existing classification of the CPA of the food industry. The baby food industry in France has shaped the science on infant and young child nutrition and nurtured long‐established relationships with health professionals. This corporate science and these relationships helped baby food companies to portray themselves as experts on child‐related topics. The baby food industry has also engaged with a broad range of civil society organisations, particularly through the concept of the first 1000 days of life, and during the covid‐19 pandemic. We found evidence, although limited, that the baby food industry directly lobbied the French government. Since its early development in France in the 19th century, the baby food industry used its CPA to promote its products and protect and sustain its market. Our findings can be used to recognise, anticipate and address the CPA of this industry, and to minimise any negative influence it may have on babies' and mother's health. Key messages: In France, the baby food industry positions itself as a key partner of researchers, health professionals, parents, and children; it has a strong presence in scientific, medical, and civil society circles, where it disseminates pro‐industry messages and promotes its products. The industry captures science by generating corporate research and engaging external researchers and organisations; health professionals through training and information, and funding and collaborating with associations; and civil society through forging relationships with organisations and charities. These activities likely further the interests of the baby food industry by protecting and expanding its market, and by shaping public opinion, so that its products and practices are not questioned.